2022
DOI: 10.2147/amep.s370447
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ and Students’ Perceptions and Attitudes Regarding the Anatomical Knowledge of Medical Students

Abstract: Background In both the preclinical and clinical sciences, anatomy is considered as the foundation of medical education. Anatomy education serves as a foundation for clinical application and future practice of medicine. Health practitioners and students are interested in the adequacy of anatomical knowledge in clinical years since it has a direct impact on medical education and professional clinical practice. Objective To examine the opinions and attitudes of medical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The traditional teaching methods of introductory medical study courses can be modernized and transformed into innovative digital training strategies for students in medical education (Santos, Barreira, & Saad, 2022;Yang, 2023). The research conducted by Almizani et al (2022) underlined that teaching medical students requires continuous effort, and numerous measures should be taken to uphold and enhance a positive outlook toward fundamental knowledge. Physical Anthropology teaching should focus more than just anatomy and "standard" techniques (Jerković et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional teaching methods of introductory medical study courses can be modernized and transformed into innovative digital training strategies for students in medical education (Santos, Barreira, & Saad, 2022;Yang, 2023). The research conducted by Almizani et al (2022) underlined that teaching medical students requires continuous effort, and numerous measures should be taken to uphold and enhance a positive outlook toward fundamental knowledge. Physical Anthropology teaching should focus more than just anatomy and "standard" techniques (Jerković et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies that have reported variations in attitudes towards anatomy based on age and gender. 2,8 However, further research is needed to explore these associations in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy is a fundamental subject in health sciences, and its mastery is essential for healthcare professionals and students to understand the human body's structure and function. 1,2 Despite the obvious significance, undergraduate medical students have often felt challenged when undertaking the course due to a vast amount of reasons such as complexity of the topics, information overload and lack of self-directed learning skills among medical students as pointed out in literatures. 1,3,4 The perceptions of medical students on anatomy are diverse and complex since anatomy is most time considered a difficult subject to study and because each student has a different preferred method of learning.…”
Section: Introductionmentioning
confidence: 99%
“…This is because medical practitioners must have sound knowledge of the human body anatomy to conduct physical examinations, evaluate radiologic investigations, operate surgeries, and perform other medical interventions. [1][2][3] The value of anatomy education to clinical training of medical and paramedical students triggered the vertical integration of anatomical sciences with clinical training. 4,5 Moreover, anatomical sciences provide medical students with a reservoir of medical terminology that applies to all other medical sciences.…”
Section: Introductionmentioning
confidence: 99%